The mediating role of financial performance in the relationship between green accounting, leverage, and firm value in basic materials sector companies listed on Indonesia Sharia Stock Index - Idayanti, Rini; Nurlia, Nurlia (Journal of Islamic Economics Lariba, 2026)
IntroductionIn recent years, the growing emphasis on sustainability and ethical investment has prompted firms to integrate green accounting and financial management practices into their business strategies. However, evidence regarding the impact of green accounting and leverage on firm value, particularly within Islamic capital markets, remains inconclusive. This study investigates how green accounting and leverage affect firm value, with financial performance acting as a mediating variable, among basic materials firms listed on the Indonesia Sharia Stock Index (ISSI).ObjectivesThis research aims to analyze the direct and indirect effects of green accounting and leverage on firm value through financial performance. It also seeks to determine whether sustainability-oriented accounting practices contribute to firm valuation and to evaluate the mediating role of profitability in shaping these relationships within an Islamic financial context.MethodA quantitative research design was employed using panel data from six basic materials firms listed on the ISSI during 2019–2023. Green accounting was measured using environmental cost disclosure, leverage by the debt-to-equity ratio, financial performance by return on assets, and firm value by Tobin’s Q. Data were analyzed using path analysis and the Random Effect Model, supported by classical assumption and Sobel tests to assess mediation effects.ResultsThe findings indicate that green accounting and leverage do not have significant direct effects on either financial performance or firm value. However, financial performance significantly mediates the relationship between green accounting and firm value, suggesting that sustainability initiatives enhance firm valuation indirectly through profitability. In contrast, financial performance does not mediate the relationship between leverage and firm value. These results demonstrate that environmental accountability contributes to firm value when translated into financial efficiency but not through debt-financed strategies.ImplicationsThis study highlights the need for firms to integrate environmental expenditures as strategic investments rather than operational costs. It underscores the importance of aligning sustainability initiatives with financial management and governance frameworks to optimize firm value. Policymakers should strengthen regulatory incentives for environmental reporting and enhance investor awareness to bridge the gap between sustainability performance and market valuation.Originality/NoveltyThis study contributes to sustainability accounting and Islamic finance literature by empirically establishing the mediating role of financial performance in the relationship between green accounting and firm value. It provides new insights into how environmentally responsible practices create value in emerging Islamic capital markets.